The Reciprocal Impact of Brand Leveraging: Feedback Effects from Brand Extension Evaluation to Brand Evalution - Lane, Vicki; Jacobson, Robert (Marketing letters, 1997)
While the benefits that brand leveraging brings to the brand extension market have been widely discussed and documented, the reciprocal impact of this action on brand evaluation has received less attention and is the subject of greater speculation. Empirical studies have failed to uncover a reciprocal effect from extension evaluation to brand evaluation. As a result, a consensus view has emerged suggesting that established brand names are sufficiently strong so as to make them resilient or even immune to extension-induced attitude change. Our results challenge this view in that we find that: i) the reciprocal effect of brand extension evaluations on brand evaluations exists, ii) the phenomenon occurs in the presence of differing attribute cues about the extension (i.e., descriptions of brand related or distinctive product attributes) and for consumers with differing levels of need for cognition.